Preference Gaps Between Developers and Millennials in Landed Housing in Yogyakarta Urban Agglomeration - Fatima Putri Prativi; Bagaskara Bagaskara; Anisa Nurpita; Nurisqi Amalia; Anas Usman Bello (Universitas Ahmad Dahlan, Yogyakarta, 2026)
The increasing urbanization in Yogyakarta Urban Agglomeration has driven rapid residential development, especially in landed housing. This study analyzes the gap between property developers' preferences and millennial consumers' expectations in housing provision. Utilizing mixed methods, primary data were collected from 54 property practitioners through structured questionnaires and in-depth interviews. Quantitative analysis included Exploratory Factor Analysis (EFA), Pearson Correlation, and K-Means Clustering to identify dominant developer preferences. Qualitative phenomenological analysis confirmed market trends and millennial preferences. The findings reveal that developers prioritize factors such as land position, house type, and land shape, while millennial consumers emphasize affordability, accessibility, and neighborhood comfort. A comparative analysis using Principal Component Analysis (PCA) and independent ttests revealed significant preference misalignments, particularly in access to main roads and environmental quality. The study highlights the necessity for coordinated policy intervention and developer adaptation to align housing supply with millennial demands, proposing the integration of public facility proximity and price affordability into future residential planning strategies. This research contributes by highlighting the mismatch in housing value perceptions between stakeholders and consumers. Practically, these insights provide policymakers and developers with a framework for designing housing policies and projects that better integrate affordability, accessibility, and livability, ensuring that they meet the housing needs of millennials.